Gerakan Bersama Pemberantasan Sa GEBER PSN (GERAKAN BERSAMA PEMBERANTASAN SARANG NYAMUK) SEBAGAI UPAYA PENCEGAHAN PENYAKIT DEMAM BERDARAH DENGUE DI DUSUN KAUMAN LABUHAN SUMBAWA: GEBER PSN (GERAKAN BERSAMA PEMBERANTASAN SARANG NYAMUK) SEBAGAI UPAYA PENCEGAHAN PENYAKIT DEMAM BERDARAH DENGUE DI DUSUN KAUMAN LABUHAN SUMBAWA - Abdul Hamid hamid; Hamdin; Iga Maliga (CV. Multi Kreasi Media, 2022)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus which is transmitted from person to person through the bite of the Aedes aegypti mosquito. Kauman Hamlet Labuhan Sumbawa Kec. Labuhan Badas Sumbawa NTB is one of the residential areas that has data on dengue fever every year, and in 2021 there were 7 cases of dengue fever. GEBER PSN or Joint Movement for the Eradication of Mosquito Nests. This movement is an effort to prevent the transmission of dengue disease caused by the Aedes aegypti mosquito. The target of this community service activity is the community members of the Kauman Hamlet, Labuhan Sumbawa, Kec. Sumbawa Regency. Sumbawa, with the aim of inviting the community to participate in the Geber PSN activity while the benefits of this community service activity are to increase public awareness about PSN as an Effort to Prevent Dengue Hemorrhagic Fever (DHF). This activity was held on April 16, 2022 in Kauman Hamlet, Labuhan Sumbawa, Kec. Sumbawa Regency. Sumbawa by involving the community and students of the S1 Public Health Study Program STIKES Griya Husada Sumbawa. The result of this activity is the implementation of Geber PSN (Joint Movement for the Eradication of Mosquito Nests) as an effort to prevent Dengue Hemorrhagic Fever in Kauman Hamlet, Labuhan Sumbawa by inviting and increasing public awareness about PSN as an Effort to Prevent Dengue Hemorrhagic Fever (DHF).